Tradisi Mambaca To Mate dalam Perspektif Pendidikan Islam: Kajian Kritis terhadap Pemahaman Teologis - Muhammad Qasim; Awaliah Musgamy; Muhammad Rusydi; Abul Khair (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
The mambaca to mate tradition is a cultural practice of the Mandar people in West Sulawesi, which still survives today as a form of respect and prayer for family members who have passed away. This practice is rich in social and spiritual values, but on the other hand, it also has the potential for theological distortion that could affect the purity of the community's faith if not examined critically. This study aims to describe the symbolic meaning, social function, and Islamic educational values contained in the mambaca to mate tradition, while also critically analyzing the community's misconceptions from an Islamic education perspective. The method used is qualitative research with a library research design, analyzing various primary sources such as contemporary literature, as well as secondary sources like scientific journals and relevant books. Research results show that this tradition has a strong social function, such as strengthening friendship and solidarity, as well as containing Islamic educational values that include spiritual aspects (ubudiyah), morality (akhlakul karimah), and discipline (nizhamiyah). However, there are also misunderstandings in the community, such as the belief that the spirits of the deceased physically appear, taste the provided offerings, or will cause disturbances if the tradition is not carried out—beliefs that contradict the principle of tauhid and can potentially lead to hidden shirk. This research implies the need for active roles from religious leaders and educators in clarifying the essential meaning of the tradition as a means of worship and local wisdom, rather than as a ritual based on fear of supernatural beings, so that this tradition can continue to be preserved without compromising the purity of Islamic creed.